Relationship between two solidification problems in order to determine unknown thermal coefficients when the heat transfer coefficient is very large - Salva, Natalia Nieves; Tarzia, Domingo Alberto (Elsevier Science Inc., 2024)
Fil: Salva, Natalia Nieves. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional del Comahue; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina